2006
DOI: 10.1053/j.seminoncol.2006.10.014
|View full text |Cite
|
Sign up to set email alerts
|

The Angiogenic Switch Molecule, Secreted FGF-Binding Protein, an Indicator of Early Stages of Pancreatic and Colorectal Adenocarcinoma

Abstract: Tumor angiogenesis has been related to the initiation as well as progression toward more aggressive behavior of human tumors. We will discuss genetic events underlying the initiation and progression of colorectal and pancreatic adenocarcinoma with a particular focus on the modulation of angiogenesis. A secreted fibroblast growth factor (FGF) binding protein (FGF-BP), which is an extracellular chaperone molecule for FGFs, has been shown to enhance FGF-mediated biochemical and biologic events and to be a crucial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 92 publications
0
17
1
3
Order By: Relevance
“…Активация ангиогенного переключения, эффекта, при котором суммарное влияние ангиогенных активаторов (VEGF, FGF, TNFa, MMP) перевешивает действие ингибиторов ангиогенеза (TIMP, IL-4, IFNa, Ang2), на ранних стадиях развития опухоли чаще всего ограничивает переход от небольшой патологии к серьезному заболеванию. И хотя рак поджелудочной железы не относится к опухолям с большим количеством кровеносных сосудов, одной из его особенностей является значительное усиление опухоль-зависимого неоангиогенеза [50,51].…”
Section: непрямые эффекты Fgf при канцерогенезеunclassified
“…Активация ангиогенного переключения, эффекта, при котором суммарное влияние ангиогенных активаторов (VEGF, FGF, TNFa, MMP) перевешивает действие ингибиторов ангиогенеза (TIMP, IL-4, IFNa, Ang2), на ранних стадиях развития опухоли чаще всего ограничивает переход от небольшой патологии к серьезному заболеванию. И хотя рак поджелудочной железы не относится к опухолям с большим количеством кровеносных сосудов, одной из его особенностей является значительное усиление опухоль-зависимого неоангиогенеза [50,51].…”
Section: непрямые эффекты Fgf при канцерогенезеunclassified
“…7 The observed increased expression of FGF-BPs at early stages of the development of pancreatic and colorectal adenocarcinomas suggested that they could be used as a diagnostic screening method for detection of premalignant cancers, provided that they are released into the circulation of these patients. 9 Most importantly, at least FGF-BP1 seems to play a functional role in tumorigenesis. Thus, it was shown in xenograft models for human cervical squamous cell carcinoma and colon adenocarcinoma that ribozyme-mediated suppression of FGF-BP expression inhibits angiogenesis-dependent tumor growth.…”
Section: Fibroblast Growth Factor-binding Proteinsmentioning
confidence: 99%
“…L'altération du 4p est associée de manière récurrente à un mauvais pronostic [11,12]. Nos résultats suggèrent qu'une inactivation par bi-mutation ponctuelles favoriserait l'acquisition du pouvoir métastatique.…”
Section: Modulations Du Pouvoir Métastatique Déterminé Par La Mutatiounclassified
“…Nos résultats suggèrent qu'une inactivation par bi-mutation ponctuelles favoriserait l'acquisition du pouvoir métastatique. Le gène de la FGF-binding protein, localisé en 4p11, et de mauvais pronostic dans les cancers coliques et pancréatiques, pourrait être le gène impliqué [12]. Sa mutation très précoce surviendrait juste après celle d'APC et modifierait la disponibilité des protéines de la famille FGF dont le gradient morphogénique régule la différenciation et la polarisation cellulaires [3].…”
Section: Modulations Du Pouvoir Métastatique Déterminé Par La Mutatiounclassified